THE UTILIZATION OF UNWRITTEN LAWS IN BANKRUPTCY DISPUTES - M. Hadi Shubhan (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2019)
Unwritten laws hold a strategic role in bankruptcy dispute settlement, both in the act of bankruptcy and in the management and settlement of a bankruptcy estate after the debtor is declared bankrupt.This paper will discuss about the characteristics of Indonesia bankruptcy law and the legal basis and theoretical basis for the possibility of using unwritten law in bankruptcy cases. This research employed a doctrinal legal research method with a statute approach, a conceptual approach, and a case approach. In Article 8 paragraph (6) of Law No. 37 of 2004 made it possible for judges to use an unwritten law as the basis in deciding on act of bankruptcy. Similarly, in regard to the management and settlement of a bankruptcy estate, some norms provide some space for the supervisory judge's and curators to make a decision or take action based on the principles of unwritten justice. In a number of court decisions, the law has also not been written down in consideration of its law.